Nanoscale Zinc Hydroxyapatite (ZnHA) Particles for Bone Tissue Engineering - Faiz Noor Haris, Noorainol; Che Murad, Mardziah; Rozlin Nik Masdek, Nik (International Journal of Engineering and Technology, 2018)
The aim of this paper is to discuss the differences in the structural properties of pure hydroxyapatite (HA) and zinc hydroxyapatite (ZnHA) nanoparticles. In this current research, nanosized HA and ZnHA were synthesised via chemical precipitation method with the use of ammonium dihydrogen phosphate, calcium oxide, zinc nitrate and distilled water. The temperature during synthesis process was maintained at 90 0C while the mixture stirred vigorously. The powders were then dried in the oven and calcined in a conventional high temperature furnace at 700 0C with varied soaking time of 2 and 3 hours for comparison purposes. The synthesised HA and ZnHA powders were subsequently characterised for thermal behaviour, phase composition and morphology examination using the Thermogravimetric Analyser (TGA), X-ray diffraction (XRD) and Field Emission Scanning Electron Microscopy (FESEM), respectively. From the XRD analysis, it was observed that the crystallinity of pure HA and ZnHA powders greatly increase after the calcination process. This can be indicated by the higher and rising intensities of the three main HA peaks in the XRD patterns. Even though the effect of soaking time during calcination did not seem very prominent from the diffraction spectra, its effect on the particle size can be seen clearly from the FESEM images. On the other hand, FESEM evaluation also shows that both HA and ZnHA nanoparticles are spherical in shape with the former powders having bigger size of particles.Â